Assessment of Facilities Key Performance Indicator (KPI) of Physiotherapy Spaces Toward the Stroke Patients’ Recovery in Putrajaya Hospital - Ishak, Mohd Hafizal (Research in Management of Technology and Business, 2022)
Key Performance Indicators (KPI) are the best tool to achieve organizational goals because KPI lets people gather knowledge. Performance measures the quality of treatment and effectiveness of various services in the healthcare sector in order to decrease costs and provide value to the patient. The stroke recovery process involves a variety of involvement that is related to stroke to ensure the stroke patients’ recovery has improved over time. Therefore, recognizing what stroke patients have improved in their recovery while using the facilities in physiotherapy space is significant to associate with facilities KPI. The purpose of this study is to identify the facilities KPI of physiotherapy spaces in the healthcare sector and to assess facilities KPI physiotherapy spaces with stroke patients’ recovery. The researcher gather data through an interview with a healthcare professional. The study discovered the facilities key performance indicator (KPI) of physiotherapy spaces in healthcare sector and assessment of facilities KPI physiotherapy spaces with stroke patients’ recovery. The data was then used to highlight the link between the facility's KPI and the recovery of stroke patients.